STUDI EKSPERIMEN PERPINDAHAN PANAS KONVEKSI PAKSA INTERNAL PADA SALURAN BENTUK SILINDER DAN PERSEGI - Qurniawan Zen Al Faris; Arrad Ghani Safitra; Setyo Nugroho (PROSIDING SNAST, 2018)
Forced convection inside a pipe is a case of convection mass transfer for internal flow. Main parameter of internal flow forced convection is a convection coefficient number (h). One of the ways to increasing the convection coefficient number is changing the cross section of the channel. But, there are some other factors that affect the convection coefficient number such as fluid velocity, surroundings temperature, and the number of heat flux. The study was conducted experimentally by making a channel from aluminum with cylinder and square cross section form. With 1.5 m length hydraulic diameter 0.0762 m, which aims to find out the characteristics of internal flow forced convection heat transfer. The channel surface is fully isolated to minimize the value of heat losses caused by the ambient temperature, so that the same thermal energy is obtained along the channel. Heating on the surface of the channel uses an electric heater with a capacity of 223.52 watts. Then the air fluid is channeled through the channel at a speed of 3.6 m / s and 5 m / s using an electric blower regulated by a valve. Testing is carried out in a room where the temperature is conditioned, taking temperature data using a temperature sensor (thermistor) within 25 cm of each sensor mounted on the surface of the channel wall. Data processing uses software engineering equation solver (EES) to improve the analysis of experimental results. From the analysis results obtained, the square channel convection coefficient number is greater than the cylinder form channel of 22,84; 22,77; 22,72; 22,7; 22,69; 22,72 W / m2K.